Gene Expression Profiling of Transcription Factors of Helicobacter pylori under Different Environmental Conditions - De la Cruz, Miguel A.; Ares, Miguel A.; von Bargen, Kristine; Panunzi, Leonardo G.; Martínez-Cruz, Jessica; Valdez-Salazar, Hilda A.; Jiménez-Galicia, César; Torres, Javier (Frontiers in Microbiology, 2017)
Helicobacter pylori is a Gram-negative bacterium that colonizes the human gastric mucosa and causes peptic ulcers and gastric carcinoma. H. pylori strain 26695 has a small genome (1.67 Mb), which codes for few known transcriptional regulators that control bacterial metabolism and virulence. We analyzed by qRT-PCR the expression of 16 transcriptional regulators in H. pylori 26695, including the three sigma factors under different environmental conditions. When bacteria were exposed to acidic pH, urea, nickel or iron, the sigma factors were differentially expressed with a particularly strong induction of fliA. The regulatory genes hrcA, hup and crdR were highly induced in the presence of urea, nickel and iron. In terms of biofilm formation fliA, flgR, hp1021, fur, nikR and crdR were induced in sessile bacteria. Transcriptional expression levels of rpoD, flgR, hspR, hp1043 and cheY were increased in contact with AGS epithelial cells. Kanamycin, chloramphenicol and tetracycline increased or decreased expression of regulatory genes, showing that these antibiotics affect the transcription of H. pylori. Our data indicate that environmental cues which may be present in the human stomach modulate H. pylori transcription.